ABOUT SOME FEATURES OF THE APPROACHES OF THE USA AND RUSSIA IN THE MEASUREMENT OF THE ACTIVITIES OF TERRORIST ORGANIZATION ISIL - Stanislav Igorevich Sergeev (Современная наука и инновации)
Jhe article examines some features of the revitalization of the terrorist organization ISIS, its cooperative ties with other extremist groups. Analyzed the approaches of Russia and the USA in the measurement ofthe activities of ISIL and its supporters, the measures of opposition to the expansion and strengthening of ISIS, as threat to international security.